Outsourced revocable identity‐based encryption from lattices. Issue 11 (22nd October 2018) - Dong, Chengcheng; Yang, Kang; Qiu, Jian; Chen, Yuanfang
Abstract: With the popularization of mobile devices, the security of wireless industrial communication technology is becoming more and more important to the information exchange of industrial production. Identity‐based encryption (IBE) is an essential branch of public key encryption, which simplifies the management of public key infrastructure. However, if these IBE cryptosystems need to revoke users, the computational overheads of the private key generator (PKG) will be substantial. In this work, in order to solve the critical issue related to revocation, we are the first to introduce outsourcing computation into lattice‐based revocable IBE (RIBE) and propose a outsourced revocable lattice‐based IBE (OR‐LIBE) scheme. In our model, most of PKG's offloads are delegated to a semitrusted cloud service provider (CSP). The scheme divides the private key into an identity component and a time component, which are generated by PKG and key update CSP (called KU‐CSP), respectively, but PKG must distribute a corresponding identity outsourcing key O K id to KU‐CSP. Our scheme is more efficient for user revocation than the previous lattice‐based RIBE schemes. Compared with the classic RIBE scheme, our scheme is resistant against quantum attacks. The proposed scheme is adaptively secure under the standard model, and its security can be reduced to hardness of learning with errors assumption. Our scheme can be applied to wireless industrial communication technology to improve the security of communication data. Abstract : In our model, most of overheads of the private key generator (PKG) are delegated to a semitrusted cloud service provider (CSP). The scheme divides the private key into an identity component and a time component, which are generated by PKG and key update CSP (KU‐CSP), respectively, but PKG must distribute a corresponding outsourcing key OKid to KU‐CSP. Compared with the classic RIBE scheme, our scheme is resistant against quantum attacks. The proposed scheme is adaptively secure under the standard model.